The Effectiveness Of The Guideline For Adjudicating Criminal Cases Based On Restorative Justice By The Supreme Court Of The Republic Of Indonesia - Flora, Henny Saida (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to analyze aspects of legal effectiveness related to the formulation of Perma RJ 2024. This research is normative legal research by prioritizing conceptual and statutory approaches. The research results confirm that the essence of Perma RJ 2024 is related to the idea of RJ which actually includes efforts to emphasize the role, participation and activeness of judges so that the RJ approach can run optimally. Perma RJ 2024 actually fulfills the three aspects of effective legal rules as stated by Anthony Allott, namely preventive nature, which is relevant to the substance of Perma RJ 2024 to educate perpetrators so that they do not repeat their actions. In the aspect of legal rules regulating clearly and firmly so that they are oriented towards resolving disputes (curatively) effectively and without being complicated, it is also relevant to Perma RJ 2024 which has emphasized the role and activeness of judges in carrying out RJ. In the aspect of legal rules, it is able to provide facilities for legal subjects to carry out legal actions (facilitative) through the formulation of norms and legal substance that are relevant and applicable in society. This is also relevant to Perma RJ 2024 which provides for the involvement of various parties in RJ, such as the perpetrator's parents. /victims, religious leaders, and community leaders to work together to solve problems